ARSENIC AND COPPER UPTAKE BY CABBAGES GROWN ON POLLUTED SOILS - Nguyen Thi Kim Phuong; Nguyen Thi Dung (Universitas Gadjah Mada, 2008)
Cabbages (Brassica Juncea (L.) Czern) were grown in pot experiments on typical unpolluted and polluted soils with concentration changing from 20.50 - 50.00 mg As/kg and 156.00 - 413.00 mg Cu/kg dry soil. The results demonstrate the elevation of As and Cu in soil may lead to increased uptake by these cabbages subsequent entry into human food chain. It was found 11.84- 32.12 mg As/kg and 46.86 - 94.47 mg Cu/kg dry leaves. It has tendency increase uptake and accumulation of Cu in cabbage tissue with increasing cultivated time, whereas, it was found accumulation of As in cabbages tissue decreased with time prolonging. The quantity of As and Cu in these cabbages, were significant higher than 0.2 mg As/kg and 5.0 mg Cu/kg fresh vegetable, the permissible limit concentration in fresh vegetable. This indicated that human may As and Cu exposure occur through eating these vegetables.